Correlation of Knowledge Level and Preventing Behavior of COVID19 in Talete 1 Tomohon - Pangkey, Marverio Robert Alexander (BKM Public Health and Community Medicine, 2024)
Purpose: This study explores how preventing behavior of COVID-19 can be related to the level of knowledge from people that have different types of knowledge stages and different educational backgrounds in Talete 1 known as places of traditional market that sell extreme raw ingredients such as wild animal and some of animal that get protected based on law. Methods: A survey of 100 people who live near the traditional market called Talete 1 who get a question from a questioner that can evaluate and score the knowledge, attitude, and an action of the people with a different level of knowledge and education background to get a correlation of the level of knowledge and the preventing behavior of COVID19. Results: The analysis shows a relation between education level and COVID-19 prevention behavior (calculated value 0,509 and p-value 0,000). Conclusion: a survey that the researcher got shows a correlation between a level of knowledge and preventing COVID-19 behavior. The questionnaire results imply that people with higher education degrees are more educated on how to prevent COVID-19. From this research, we can get new lessons and suggest that we need to keep up the education in every part of Indonesia and keep promoting health information so all people can remember it.